RECURRENT BILIARY EVENTS IN PATIENTS, WHO UNDERWENT ENDOSCOPIC LITHOEXTRACTION DUE TO OBSTRUCTIVE JAUNDICE - Dolzhkovyi, S.V. (World of Medicine and Biology, 2022)
The purpose of our study was to analyze early results of successful endoscopic lithoextraction in patients with choledocholithiasis complicated with obstructive jaundice. We investigated case histories of 103 patients, who were treated with obstructive jaundice due to choledocholithiasis and have undergone endoscopic lithoextraction during last 6 months. We observed episodes of biliary pain in 29 patients, 20 cases of acute calculus cholecystitis and 3 cases of obstructive jaundice recurrence. After statistical data analysis, the following conclusions were made: 1) there is no correlation between age, sex and occurrence of acute calculus cholecystitis during first six month after endoscopic lithoextraction on account of obstructive jaundice; 2) episode of successfully treated biliary pain can be considered as a risk factor for acute calculus cholecystitis occurrence in patients after endoscopic lithoextraction; 3) time gap of four weeks after endoscopic lithoextraction seems to be relatively safe with regard to adverse biliary events occurrence and laparoscopic cholecystectomy should be performed during this interval.
Keywords: choledocholithiasis; endoscopic retrograde cholangiopancreaticography; cholecystectomy